Certified incident handler (ECIH) v2 - Gordon, Adam; Lowrie, Daniel (Packt Publishing, 2024)
The course begins with an exploration of fundamental concepts in information security and incident management, covering topics such as Vulnerability Management, Threat Assessments, Risk Management, and the NIST RMF. The course guides you through the incident handling process, from preparation to post-incident activities. Learn how to prepare for incident handling, record and assign incidents, perform incident triage, and handle notifications effectively. The curriculum covers incident containment, evidence gathering, forensic analysis, eradication, recovery, and post-incident activities. Gain hands-on experience with ethical hacking tools and techniques, preparing you to address real-world cybersecurity challenges. The course explores various security incidents, including network security, unauthorized access, inappropriate usage, denial-of-service, and web application security incidents. Additionally, delve into cloud security, insider threats, and essential security checks. Upon course completion, you'll possess critical security analysis and incident response skills, equipping you to identify, address, and prevent complex cyber threats effectively. What you will learn Develop a deep understanding of the incident handling process from preparation to post-incident activities Gain practical experience in digital evidence collection and forensic analysis Effectively manage various security incidents, including malware, network, and web application security incidents Grasp essential cloud security concepts and best practices Identify and mitigate insider threats effectively Utilize tools like OSForensics, Wireshark, and NMAP for cybersecurity tasks Audience This course is suitable for cybersecurity professionals, ethical hackers, incident responders, and individuals seeking to enhance their cybersecurity skills. A basic understanding of information security concepts is recommended. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Adam Gordon: Adam Gordon has 30+ years as an IT instructor in the private and public sectors. He holds more than 160 IT certifications. He has trained thousands of IT pros over the course of his career. He has over 160 professional and IT certifications. Daniel Lowrie: After working professionally as a systems administrator and as a network administrator, Daniel switched to IT education. His certifications include CompTIA A+, Network+, Linux+, CySA+, and PenTest+; CEH; MCSA; CFR; eJPT.
Online resource; title from title details screen (O'Reilly, viewed January 31, 2024)
Keywords: Computer networks -- Study guides -- Security measures -- Examinations; Computer security -- Study guides -- Examinations; Electronic data processing personnel -- Study guides -- Certification; Computer networks -- Access control; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Sécurité informatique; Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet